Repeated Interaction in Teams: Tenure and Performance - Villas-Boas, J. Miguel (Management Science, 2020)
Many of the activities performed in firms are done by teams, where a common output is observed, but outsiders cannot observe the individual contributions of each team member. This leads to the possibility of some of the members of the team free-riding on the contributions of others. Repeated interactions of a team can then potentially lead to cooperation among the members of the team under the credible threat of returning to a free-riding equilibrium. However, repeated interaction under cooperation of a team may lead to decreasing overall output over time because the benefits of the team working together may exogenously decrease over time. This then leads to the optimal duration of a team being finite but stochastic, creating inefficiency, but being sufficiently long so that the elements of the team have an incentive to cooperate. This provides a theory of successive team formation and termination in a firm. The possibility for a too long duration for full team cooperation may then lead the firm to reduce the extent of team cooperation, to be able to reduce the expected duration of a team, and have fewer losses of the team lasting for too long. This paper was accepted by Eric Anderson, marketing.